COMMAND RESPONSIBILITY — A CONTEMPORARY EXPOSITION (2020)
Emerging from the vestiges of World War II, the doctrine of command or superior responsibility is a form of indirect criminal liability, which purports that a commander or superior may be held criminally responsible for crimes committed by subordinates. Contemporary times may shine a different spotlight on the doctrine of command responsibility, owing to the advancements in digital technology and our constant reliance on it. It is as such an enabler of justice, but it may act as a double-edged sword for high-ranking officials seeking to flout law and commit humanitarian violations. This thesis aims to provide a contemporary exposition of the doctrine of command responsibility, the elements to be satisfied to prove such a doctrine, and the intricacies and nuances involved in proving
its scope and application in international criminal law.
Keywords: Criminal law